Agarose particle-templated porous bacterial cellulose and its application in cartilage growth in vitro. (15th January 2015) - Yin, Na; Stilwell, Matthew D.; Santos, Thiago M.A.; Wang, Huaping; Weibel, Douglas B.
Graphical abstract: Abstract: Bacterial cellulose (BC) is a biocompatible hydrogel with a three-dimensional (3-D) structure formed by a dense network of cellulose nanofibers. A limitation of using BC for applications in tissue engineering is that the pore size of the material (∼0.02–10 μm) is smaller than the dimensions of mammalian cells and prevents cells from penetrating into the material and growing into 3-D structures that mimic tissues. This paper describes a new route to porous bacterial cellulose (pBC) scaffolds by cultivating Acetobacter xylinum in the presence of agarose microparticles deposited on the surface of a growing BC pellicle. Monodisperse agarose microparticles with a diameter of 300–500 μm were created using a microfluidic technique, layered on growing BC pellicles and incorporated into the polymer as A. xylinum cells moved upward through the growing pellicle. Removing the agarose microparticles by autoclaving produced BC gels containing a continuous, interconnected network of pores with diameters ranging from 300 to 500 μm. Human P1 chondrocytes seeded on the scaffolds, replicated, invaded the 3-D porous network and distributed evenly throughout the substrate. Chondrocytes grown on pBC substrates displayed a higher viability compared to growth on the surface of unmodified BC substrates. The approach described in this paper introduces a new method for creating pBC substrates with user-defined control over the physical dimensions of the pore network, and demonstrates the application of these materials for tissue engineering.